2009
DOI: 10.1111/j.1365-2524.2008.00803.x
|View full text |Cite
|
Sign up to set email alerts
|

An emotive subject: insights from social, voluntary and healthcare professionals into the feelings of family carers for people with mental health problems

Abstract: Caring for people with mental health problems can generate a whole range of positive and negative emotions, including fear, disbelief, guilt and chaos as well as a sense of purpose, pride and achievement. This paper explores the emotions of family carers from the perspectives of social, voluntary and healthcare professionals. Sixty-five participants were interviewed, the sample included directors, managers and senior staff from social, voluntary and healthcare organisations. Participants were encouraged to tal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 32 publications
1
26
0
Order By: Relevance
“…For many carers the onset of a severe mental illness in a relative was a steep and unsupported learning curve (Gray et al . 2009).…”
Section: Resultsmentioning
confidence: 99%
“…For many carers the onset of a severe mental illness in a relative was a steep and unsupported learning curve (Gray et al . 2009).…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, scarce contact between caregivers and health professionals has been shown to increase subjective carer burden (Jacob et al 1987;Chang et al, 2010cited in Hastrup et al, 2011). Ostman and Kjellin (2002 noted that relatives who acted as carers had deep-seated feelings of inferiority to staff, which could explain low levels of cooperation between relatives and professionals as well as subsequent difficulties with access to services (cited in Gray et al, 2009). Lack of carer involvement reinforced the view of some professionals that silence means acquiescence / acceptance (Chiu et al, 2006).…”
Section: Carer Involvement and Adult Mental Healthcarementioning
confidence: 99%
“…Caring for people with SMI can generate fear, disbelief, guilt and chaos, and coping mechanisms may include the seeking of relevant information, optimism, routine living and re-evaluating social expectation (James, 1989 cited in Gray et al, 2009) Active strategies have been associated with lower levels of mental health distress amongst carers when compared to avoidance strategies. O-Doherty and Doherty (2008) conducted study with the carers of people with SMI and found few participants who combined the use of active coping strategies with avoidance strategies, leading to the suggestion that these strategies could be mutually exclusive within these relationships.…”
Section: Introductionmentioning
confidence: 99%
“…A year later, Gray proposed drawing up a covenant between mental health services and family carers, one based on mutual obligations. 7 He claimed that much of the relationship between families and services puts the interests of service users and providers ahead of family members and suggested that family members were hidden and invisible, trapped and isolated in narrow roles. Therefore, a covenant would help clarify what professionals expect of carers; and would ultimately improve engagement and relationships.…”
Section: Introductionmentioning
confidence: 99%